Neolitiske ravperler i Västergötland - Ebbesen, Klaus (In Situ Archaeologica, 2002)
Amber beads are frequently found in the Middle Neolithic megaliths of central Västergötland, Sweden. They are imported from Northern Jutland in Denmark. The distribution pattern of the amber beads as well as of thin-butted flint axes shows that they come directly from Denmark to the Scandinavian Peninsula. They are distributed by direct contact by boat - a maritime distribution that gives another ”fall-of-pattern” than landbased exchange.